À propos de l’article de M. Arnoux, « Disparition ou conservation des sources… ». Le scribe, le droit et le prince : recherche autour de l’utilisation de l’écrit juridique par les ducs de Normandie de la fin du Xe à la fin du XIe siècle - Gilduin Davy (Tabularia)
The question of the survival or the disappearance of the sources, studied by Mathieu Arnoux, stresses the problem of the continuity of the governmental executives between Carolingian Neustria and ducal Normandy. At the heart of this problem, the rediscovery of legal writing at the ducal court illustrates, as of the reign of Richard I, the new-carolingian perspective which the descendants of Rollon represent. Supporting by their auctoritas the restoration of the writing by means of their auctoritas, the dukes assert themselves as guarantors for the safeguard of the rights. However, this rebirth of the writing could not mask the persistence of oral practice in the dissemination of the normative message.